2018
DOI: 10.1002/smi.2842
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of hair cortisol concentrations in disadvantaged young children

Abstract: Children from highly disadvantaged families tend to experience worse health, educational, and job outcomes than less disadvantaged peers. However, the mechanisms underlying these relationships remain to be explicated. In particular, few studies have investigated the relationships between the psychosocial influences that children are exposed to early in life and longer term cortisol output. This study aims to contribute to the literature by exploring how disadvantaged young children's experiences of family adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…Our hypothesis that parental sensitivity would explain the effects of SES on child cortisol function was not supported. This expectation was informed by prior research linking lower parental sensitivity to higher child cortisol output, as indexed by both salivary and hair measures (Blair et al, 2011; Johnson et al, 2018; Simmons et al, 2019; Zalewski et al, 2012). In our sample, consistent with this prior work, lower parental sensitivity was associated with higher child HCC and higher bedtime SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis that parental sensitivity would explain the effects of SES on child cortisol function was not supported. This expectation was informed by prior research linking lower parental sensitivity to higher child cortisol output, as indexed by both salivary and hair measures (Blair et al, 2011; Johnson et al, 2018; Simmons et al, 2019; Zalewski et al, 2012). In our sample, consistent with this prior work, lower parental sensitivity was associated with higher child HCC and higher bedtime SCC.…”
Section: Discussionmentioning
confidence: 99%
“…A study of toddlers in low-income households reported that they had higher basal SCC if they were insecurely attached (Johnson, Mliner, Depasquale, Troy, & Gunnar, 2018). In two recent studies of preschool children, lower parent sensitivity was linked to higher child HCC (Kao, Tuladhar, Meyer, & Tarullo, 2019; Simmons et al, 2019). In another study of preschool children, parental negativity mediated the association between poverty and flatter diurnal slope (Zalewski, Lengua, Kiff, & Fisher, 2012).…”
mentioning
confidence: 98%
“…countries (Ling et al, 2019;Simmons et al, 2019). Although we cannot determine statistical significance of these mean-level differences because cross-assay and cross-ethnic comparisons can be methodologically biased (Ling et al, 2019;Rippe et al, 2016; (Gunnar & Vazquez, 2001;Koss, Hostinar, Donzella, & Gunnar, 2014;Zalewski, Lengua, Kiff, & Fisher, 2012).…”
Section: Possible Mechanismsmentioning
confidence: 94%
“…Furthermore, studies from high-income samples have found both mean-level sex differences in HCCs and some sex-specific links between HCCs and measures of children's development. Specifically, young boys have higher HCCs compared to girls (Dettenborn, Tietze, Kirschbaum, & Stalder, 2012;Gerber et al, 2017;Grunau et al, 2013;Maurer et al, 2016;Rippe et al, 2016;Simmons et al, 2019).…”
Section: Sex Differences In Hair Cortisol and Cognitive Developmentmentioning
confidence: 99%
See 1 more Smart Citation